Copyright and Patent Protection of Cloud Storage Software in the BRICS Member States - A. Klishin; K. Taran (BRICS Law Journal, 2021)
In the BRICS Member States, serious attention is paid to Information Technology development in terms of both technology and law. These countries are at the forefront in the development of the digital economy and digital innovations. Cloud storage software is an important element in this sector and is intensively applied in civil law transactions. The processes of approval, storage and sorting of documents are being automated on the basis of the relevant computer programs. This helps companies and government agencies to systemize their operations. At present, the most pressing issues are those related to copyright and copyright holders of computer programs since software code may be copied, even illegally or unconscientiously, and used as the basis for another software product. Cloud storage software is copyright-protected, but, depending on the scope of its use, additional patent protection may be required. Given the rapid development of the IT sector, a software product may be one of the components in an invention subject to patenting. The article focuses on the relationship between copyright and patent protection of software and offers a comparison of the approaches taken by the BRICS countries. Approaches taken by Germany as a European Union Member State and the United States of America are shown in the all-out comparison. The article also analyzes the views of academics on the relationship between copyright and patent protection of software.